2013
DOI: 10.5194/cp-9-1345-2013
|View full text |Cite
|
Sign up to set email alerts
|

Millennial-scale variability of marine productivity and terrigenous matter supply in the western Bering Sea over the past 180 kyr

Abstract: We used piston cores recovered in the western Bering Sea to reconstruct millennial-scale changes in marine productivity and terrigenous matter supply over the past ~180 kyr. Based on a geochemical multi-proxy approach, our results indicate closely interacting processes controlling marine productivity and terrigenous matter supply comparable to the situation in the Okhotsk Sea. Overall, terrigenous inputs were high, whereas export production was low. Minor increases in marine productivity occurred during interv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 170 publications
(312 reference statements)
5
38
0
Order By: Relevance
“…Contents of TOC, CaCO 3 , and biogenic opal in deep-sea sediments are usually used as key parameters to assess paleoproductivity (Berger et al, 1989;Narita et al, 2002;Prahl et al, 1989;Seki et al, 2004). The color b * values correlate well with the changes in biogenic opal content in sediment cores (Nürnberg and Tiedemann, 2004) and are widely used as a paleoproductivity proxy in the NW Pacific and its marginal seas Max et al, 2012;Riethdorf et al, 2013). Total carbon and inorganic carbon contents in core 41-2 were measured at every 2 cm throughout the core by coulometry using an AN-7529 analyzer in the same way, which has been reported by Gorbarenko et al (1998).…”
Section: Chlorinmentioning
confidence: 97%
See 3 more Smart Citations
“…Contents of TOC, CaCO 3 , and biogenic opal in deep-sea sediments are usually used as key parameters to assess paleoproductivity (Berger et al, 1989;Narita et al, 2002;Prahl et al, 1989;Seki et al, 2004). The color b * values correlate well with the changes in biogenic opal content in sediment cores (Nürnberg and Tiedemann, 2004) and are widely used as a paleoproductivity proxy in the NW Pacific and its marginal seas Max et al, 2012;Riethdorf et al, 2013). Total carbon and inorganic carbon contents in core 41-2 were measured at every 2 cm throughout the core by coulometry using an AN-7529 analyzer in the same way, which has been reported by Gorbarenko et al (1998).…”
Section: Chlorinmentioning
confidence: 97%
“…Previous studies also found the occurrence of increased export of productivity during the period of millennial-scale climate and environmental ameliorations, correlated with DO interstadials, in the Okhotsk and Bering seas Kim et al, 2011;Riethdorf et al, 2013;Seki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) is presented in detail in Max et al (2012). These records are part of a stratigraphic framework for the subarctic northwest Pacific and its marginal seas (Riethdorf et al, 2013). In general, it is based on detailed core-to-core correlations using high-resolution XRF measurements and core-logger data, further constrained by 40 planktic foraminiferal AMS 14 C datings spanning the time interval of the last deglaciation.…”
Section: Chronologymentioning
confidence: 99%